Cloud and IoT Technologies Revolutionizing Precision Agriculture - Anand Kumar Vedantham (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Integrating Cloud Computing and Internet of Things (IoT) technologies is revolutionizing the agricultural sector by enabling precision farming practices and data-driven decision-making. This comprehensive article explores the transformation of traditional farming through smart agriculture technologies, examining the technological infrastructure, key applications, and measurable benefits. The article discusses how IoT sensor networks, cloud-based analytics, and automated systems enhance resource optimization, environmental sustainability, and operational efficiency. The article demonstrates that these technological implementations significantly impact water conservation, crop health monitoring, field mapping, equipment management, and environmental protection while delivering substantial economic benefits through improved yields and reduced operational costs. The article provides insights into the current state of smart agriculture adoption and its implications for future farming practices.